ETIKA MAKAN DAN MINUM PERSPEKTIF HADIS DAN IMPLIKASI TERHADAP SISTEM PENCERNAAN - Birrun Walidaini (LPPM IAI Hasanuddin Pare-Kediri, 2026)
The Prophet’s hadiths provide a comprehensive explanation of the function of the Qur’an, not only as guidance for life but also as a means of healing for both the body and the soul. Moreover, these hadiths are found in Ṣaḥīḥ Muslim, one of the primary canonical collections regarded as authoritative literature in the field of hadith. This study aims to examine and analyze the hadiths that are related to and have implications for the digestive system, as well as to understand their relevance within the context of modern Islamic medicine. The research employs a qualitative approach using library research, with thematic analysis of the relevant hadiths found in the primary collections (al-kutub al-mu‘tabarah). The analysis includes an examination of both the sanad (chain of transmission) and the matan (text) of the hadiths. The findings show that the hadith prohibiting eating and drinking while standing represents a preferred ethic of conduct rather than an absolute prohibition, as there are authentic narrations indicating that it is permissible in certain circumstances. From a health perspective, sitting while eating or drinking is considered more comfortable and supportive of the digestive process, although scientific evidence on this matter remains inconclusive. Thus, the teachings of the Prophet emphasize the importance of proper etiquette, caution, and flexibility in everyday practice.